Anatomia comparada do xilema secundário de clones de Eucalyptus sp. (Myrtaceae) - Ferreira, Cassiana Alves (2017)
Although the anatomy of the secondary xylem of the plants is of great importance for the identification of wood species devoid of vegetative organs, the academic community has always used the anatomy with careful, since the morphological plasticity that the cellular elements may suffer, is due to age the plant or the environment to which it is subjected, can mask its identity. However, today after several studies it is already possible to identify some morphological alterations as a function of the age of the plant or environment, and the question arises: with the knowledge of theses variations it is possible to separate Eucalyptus genotypes based only on parameters of wood anatomy? In this context, the present study aims to identify anatomical parameters that can segregate the genotypes, as well as relate them to the environment in which they inhabit, in order to verify the influence of the environment under these parameters. The material used for the present study was collected in three city of the state of Minas Gerais and the anatomical analyzes followed those recommended by the IAWA committee for wood anatomy, for microfibrillary angle analysis the methodology adopted was polarized light and to measure the angle of the perforate plate was used the method of individualized vessel elements. The anatomical parameters that segregated the Eucalyptus genothypes were the types of axial parenchyma, growth layers, presence of tilose and contents in the radial cells. The relationships between fiber biometry and the microfibrillary angle were established in the present study, as well as the relationships between the parameters of the tracheal elements and the inclination of perforate plate, according to the genotype.